INNOVATION IN THE FOOD SECTOR: WHAT CONSUMERS THINK ABOUT NEW PRODUCTS? - Cheung, Thelma Lucchese; Goulart, Gislayne da Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This article presents information about consumers’ perceptions an innovative food product, the cheese bread with carrots. consumers who live in the city of campo grande were interviewed and asked about the product created by experts from senai / ms. approximately five hundred men and women over 18 years and different socioeconomic levels were included in the sample of the study. the statistical treatment of the data collected allowed us to understand that the original cheese bread is a product that raises the diners the idea of speed, ease of preparation and enjoyment in consumption. it was noticed that talking about a hunk of cheese different from the original, for example, with carrot, left undecided, anxious and confused consumers. to be placed on the market will require effective communication of the product is performed by diverting the natural character of the innovative product of the motto of their communication.